2008
DOI: 10.1007/s11240-008-9364-2
|View full text |Cite
|
Sign up to set email alerts
|

Efficient somatic embryogenesis in sugar beet (Beta vulgaris L.) breeding lines

Abstract: Efficient regeneration via somatic embryogenesis (SE) would be a valuable system for the micropropagation and genetic transformation of sugar beet. This study evaluated the effects of basic culture media (MS and PGo), plant growth regulators, sugars and the starting plant material on somatic embryogenesis in nine sugar beet breeding lines. Somatic embryos were induced from seedlings of several genotypes via an intervening callus phase on PGo medium containing N 6 -benzylaminopurine (BAP). Calli were mainly ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
18
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 47 publications
2
18
0
Order By: Relevance
“…The frequencies of somatic embryo formation were previously shown to vary among genotypes in sugar beet cultivars and breeding lines (Abe et al 1991;Doley and Saunders 1989;Saunders and Shin 1986;Zhang et al 2008), so these results may reflect genetic differences, as we hypothesized for the callus formation. There was no significant correlation between PEC and PSE (r=0.15; Figure 4).…”
Section: Discussionmentioning
confidence: 79%
See 2 more Smart Citations
“…The frequencies of somatic embryo formation were previously shown to vary among genotypes in sugar beet cultivars and breeding lines (Abe et al 1991;Doley and Saunders 1989;Saunders and Shin 1986;Zhang et al 2008), so these results may reflect genetic differences, as we hypothesized for the callus formation. There was no significant correlation between PEC and PSE (r=0.15; Figure 4).…”
Section: Discussionmentioning
confidence: 79%
“…We found that PEC varied widely, ranging from 0 to 88.9%, with relatively continuous variation (Table 1). It was previously recognized that the frequencies of embryogenic callus formation in sugar beet cultivars and breeding lines depended on the kinds of explants that were used (Roussy et al 1996;Zhang et al 2004) or their genotypes (Abe et al 1991;Doley and Saunders 1989;Saunders and Shin 1986;Yu 1989;Zhang et al 2004Zhang et al , 2008. These results may reflect differences in the levels of endogenous plant hormones in the explants or in various genetic factors that control callus formation in the breeding lines.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, the immature embryos and cotyledons of peach (Prunus persica L.) [4], the young embryos of cherry (Prunus avium L.) [5], the leaves of apple (Malus pumila Mill.) [6], the embryos of sugar beet (Beta vulgaris L.) [7], the young leaves of Bartlett (Pyrus communis L.) [8], the flowers of chrysanthemum (Dendranthema morifolium) [9], the leaves of carnation (Dianthus caryophyllus L.) [10] (Yantcheva A. et al, 1998), the scale leaves of lily (Lilium brownii var. viridulum) [11], the tender leaf of Kalanchoe blossfeldiana [12], and the leaves of Alaenopsis orchid [13] could all induce the somatic embryos to form regeneration plants.…”
Section: The Direct Se Pathwaymentioning
confidence: 99%
“…Furthermore, natural variations in Arabidopsis have been used extensively for molecular genetic studies of developmental and physiological processes (Alonso-Blanco et al 2009;Koornneef et al 2004 collection and used for quantitative trait loci analysis of seed germinability (Meng et al 2008), flowering time (Werner et al 2005), light sensitivity (Maloof et al 2001), and leaf architecture (Pérez-Pérez et al 2002). Because somatic embryogenesis is strongly influenced by genotype in many plant species (Brown and Atanassov 1985;Hiraga et al 2007;Sharma and Rajam 1995;Zhang et al 2008), characterization of Arabidopsis accessions with differing capacities for somatic embryos is helpful for investigating molecular mechanisms of somatic embryogenesis. RIKEN BioResource Center preserves over 340 natural accessions collected worldwide and is characterizing morphological and physiological properties of all individual accessions.…”
mentioning
confidence: 99%